The importance of a collection development policy for the school library (Synergy, 2023)
Kumari Macdougall, a librarianship student at Charles Sturt University, explores the importance of creating a collection development policy to assist in the smooth running of the library service. Kumari describes the impact of a CDP and its relevance to all areas of the library’s operations.